It doesn’t make sense, but we do: framing disease in an online metastatic breast cancer support community - Ariane B. Anderson (Qualitative Research in Medicine & Healthcare, 2019)
Using Weick’s sensemaking as a conceptual framework to investigate online discussions between members of a Facebook group of metastatic breast cancer patients, and using thematic analysis to examine textual threads between group members, this research examines participants’ framing of cancer survivorship. Participants in peer-to-peer disease support groups, which are not led by medical experts, communicate differently among themselves in order to cope with chronic and terminal illness. Perceptions of survivorship of late stage patients versus early stage patients differ for a variety of reasons, with late stage patients understanding their illness trajectory more often as chronic and declining. This analysis identified three properties of sensemaking used by members to manage their disease: identity, retrospective, and enactment. Results indicate that peer-to-peer online support group communication engenders distinct framing logics that members draw upon for group support as they manage a chronic and terminal disease.